Social and legal nature of the penalty of life imprisonment - Shidlovsky, Andrei V. (Journal of the Belarusian State University. Law, 2019)
The article is investigating the origins of the idea of life imprisonment in the Belarusian criminal law. Also it is proved that this type of punishment is a kind of deprivation of liberty for the content of punitive legal restrictions, because the main unifying feature between them is one – the isolation of the convict from society. The content of this punishment is revealed through a set of significant restrictions and deprivations of one of the most valuable benefits of man – his personal freedom. The article reveals the aim of criminal responsibility when using the life imprisonment, which is focused on achieving the maximum preventive effect – the implementation of private and general prevention, and also involves a correctional process, as a result in the law-abiding behavior of the convicted person. There are identified the directions of using the elements of new trends in execution of such punishment (in the one hand improvements and on the others deterioration of the terms of serving this sentence).
Keywords: punishment; life imprisonment; imprisonment; trend system; correctional process; isolation from a society; convicted person